Multigene Phylogeography of Bactrocera caudata (Insecta: Tephritidae): Distinct Genetic Lineages in Northern and Southern Hemispheres - Yong, Hoi Sen; Lim, Phaik Eem; Tan, J.; Song, Sze Looi; Suana, I.W.; Eamsobhana, P. (Public Library of Science, 2015)
Bactrocera caudata is a pest of pumpkin flower. Specimens of B. caudata from the northern hemisphere (mainland Asia) and southern hemisphere (Indonesia) were analysed using the partial DNA sequences of the nuclear 28S rRNA and internal transcribed spacer region 2 (ITS-2) genes, and the mitochondrial cytochrome c oxidase subunit I (COI), cytochrome c oxidase subunit II (COII) and 16S rRNA genes. The COI, COII, 16S rDNA and concatenated COI+COII+16S and COI+COII+16S+28S+ITS-2 nucleotide sequences revealed that B. caudata from the northern hemisphere (Peninsular Malaysia, East Malaysia, Thailand) was distinctly different from the southern hemisphere (Indonesia: Java, Bali and Lombok), without common haplotype between them. Phylogenetic analysis revealed two distinct clades (northern and southern hemispheres), indicating distinct genetic lineage. The uncorrected 'p' distance for the concatenated COI+COII+16S nucleotide sequences between the taxa from the northern and southern hemispheres ('p' = 4.46-4.94%) was several folds higher than the 'p' distance for the taxa in the northern hemisphere ('p' = 0.00-0.77%) and the southern hemisphere ('p' = 0.00%). This distinct difference was also reflected by concatenated COI+COII+16S+28S+ITS-2 nucleotide sequences with an uncorrected 'p' distance of 2.34-2.69% between the taxa of northern and southern hemispheres. In accordance with the type locality the Indonesian taxa belong to the nominal species. Thus the taxa from the northern hemisphere, if they were to constitute a cryptic species of the B. caudata species complex based on molecular data, need to be formally described as a new species. The Thailand and Malaysian B. caudata populations in the northern hemisphere showed distinct genetic structure and phylogeographic pattern.